CHRONIC INTERMITTENT HYPOXIA AFFECTS INTEGRATION OF SENSORY INPUT BY NEURONS IN THE NUCLEUS TRACTUS SOLITARII - Kline, David D. (2010)
The autonomic nervous and respiratory systems, as well as their coupling, adapt over a wide range of conditions. Chronic intermittent hypoxia (CIH) is a model for recurrent apneas and induces alterations in breathing and increases in sympathetic nerve activity which may ultimately result in hypertension if left untreated. These alterations are believed to be due to increases in the carotid body chemoreflex pathway. Here we present evidence that the nucleus tractus solitarii (nTS), the central brainstem termination site of chemoreceptor afferents, expresses a form of synaptic plasticity that increases overall nTS activity following intermittent hypoxia. Following CIH, an increase in presynaptic spontaneous neurotransmitter release occurs under baseline conditions. Furthermore, during and following afferent stimulation there is an augmentation of spontaneous transmitter release that occurs out of synchrony with sensory stimulation. On the other hand, afferent evoked synchronous transmitter release is attenuated. Overall, this shift from synchronous to asynchronous transmitter release enhances nTS cellular discharge. The role of the neurotransmitter dopamine in CIH-induced plasticity is also discussed. Dopamine attenuates synaptic transmission in nTS cells by blockade of N-type calcium channels, and this mechanism occurs tonically following normoxia and CIH. This dopaminergic pathway, however, is not altered in CIH. Taken together, alterations in nTS synaptic activity may play a role in the changes of chemoreflex function and cardiorespiratory activity in the CIH apnea model.